Anthelmintic Drug Resistance of Gastrointestinal Nematodes of Naturally Infected Goats in Haramaya, Ethiopia - Anteneh Wondimu; Yehualashet Bayu (Journal of Parasitology Research)
Gastrointestinal parasites and their anthelmintic resistance are major constraints to goat production in Ethiopia. Experimental investigation by faecal egg count reduction test (FECRT) and larval cultures were used to assess the occurrence of anthelmintic resistance in naturally infected goats with gastrointestinal nematodes (GIN) in Haramaya, Ethiopia. One hundred goats with a minimum of 150 eggs per gram (EPG) count were selected and randomly divided into five groups, 20 goats in each group, four treated and one untreated group. The result of the faecal egg count reduction test percentage (FECRT%) and the lower 95% confidence limit showed the presence of anthelmintic resistance for all tested drugs except tetramisole. FECRT% and lower 95% confidence limit were 69.9% and 36.9 for albendazole, 84.3% and 66.1 for tetraclozan, 95.7% and 87.4 for tetramisole, and 71.1% and 38.2 for ivermectin, respectively. Trichostrongylus, Teladorsagia, and Haemonchus showed anthelmintic resistance for tested drugs. Coproculture from different treatment groups revealed Trichostrongylus (69.2% in ivermectin and 59.6% in albendazole) were the predominant nematode followed by Teladorsagia (21.9% in albendazole and 14.7% in ivermectin). In tetraclozan treatment group, Trichostrongylus (42%) and Teladorsagia (41.3%) were comparable, followed by Haemonchus (13%). In group treated with tetramisole, Teladorsagia (54.3%) were the most frequently detected nematode followed by Trichostrongylus (25.7%) and Haemonchus (11.4%). Therefore, this study demonstrated the presence of multidrug resistant nematodes that may limit the productivity of goats. Moreover, further studies covering wider areas of Ethiopia and mechanisms of nematode resistance need to be studied in the future.